Intelligibility-based Instruction and English as a lingua franca - Hodgetts, John (Research in Language, 2025)
This paper draws heavily from my previous work on intelligibility (Hodgetts, 2020). It advocates basing pronunciation instruction on intelligibility goals, rather than native-like production goals and investigates the research available on the segmental and suprasegmental features that should be prioritized in order to enhance intelligibility and comprehensibility. First, the Chapter defines and explains the concepts of intelligibility, comprehensibility and accentedness, before discussing the merits of native and intelligibility-based targets of instruction in various contexts. It then examines which elements of segmental and suprasegmental language instruction might be included in an intelligibility-based syllabus. The crucial role of the listener is explored, as is the issue of English used as a lingua franca.